Desalination of Red Sea water using both electrodialysis and reverse osmosis as complementary methods - E.A. Abdel-Aal; M.E. Farid; Fatma S.M. Hassan; Adila E. Mohamed (Egyptian Journal of Petroleum)
Desalination process separates nearly salt free water from sea or brackish water. So, desalination process is becoming a solution for water scarcity all over the world. Two membrane methods of water desalination namely electrodialysis (ED) and reverse osmosis (RO) are used in this study as complementary methods. The results show that both ED and RO can be used as integrated system. This system is economic and cost effective compared with each individual method provided using the ED system before the RO. In this study, it was approved that seawater can be used as it is an electrolyte. TDS of Red Sea water was decreased from 42070 ppm to 2177 ppm achieving 94.8% removal efficiency using ED for half of its optimum time. Total removal efficiency of 99.4% can be obtained using the combined system of ED and RO.